Biogas production from the perspective of sustainable development - PAWLITA-POSMYK, Monika; WZOREK, Małgorzata (Economic and Environmental Studies, 2020)
One of the basic aspects of sustainable development strategy involves investments in green technologies, including energy production from renewable sources. Biomass, special organic waste which belongs to “green sources” of energy can be used in the methane fermentation process of biogas production to generate heat and electricity. Biogas power plants have functioned in the Polish energy industry for many years now. On the basis of the data available from Central Statistical Office, in 2014 the ratio of biogas accounted for 7.6% of the structure of primary energy derived from renewable sources in the EU and 2.6% in Poland. An important consideration related to the production of biogas is associated with the applicability of waste resources derived from agricultural production and from the food industry, including pig slurry, slaughterhouse waste, brewing and distilling dregs as well as others. The operation of biogas plants provides considerable benefits to the environment, resulting from the controlled fermentation process and its application in the production of useful energy, as it can provide reduction of the emission of methane and other greenhouse gases. The aspects including the reduction of the volume of waste, environmental protection, fulfillment of the EU obligations and local energy security, form the reasons why communes in Poland should focus their attention on the use of biogas. This paper presents the results of SWOT analysis of biogas production in the context of sustainable development. The assessment of the aspects (strengths, weaknesses, opportunities and threats) and the intensity of their impact were undertaken on the basis of a point scale developed by the authors. The analysis shows that the process demonstrates a number of strengths, which can promote the implementation of positive changes in the environmental and social aspects undertaken on a local scale.